PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MENGGUNAKAN MEDIA SMART APPS CREATOR PADA HASIL BELAJAR MATA PELAJARAN FIQIH MENNGGUNAKAN METODE RESARCH AND DEVELOPMEN (RND) - Wahyuto Sejati, Dewi; Hardi (Abdi Teknoyasa, 2023)
This research is the development of smart apps creator media. Where the research aims to determine the feasibility and effectiveness of learning using smart apps creator media. The study used the RnD method and the Pairet Sample Test. From the results of media expert validation the total percentage is 86%, from Material Expert Validation is 84% and student acceptance of the media is 82%. Therefore, smart apps creator media is suitable for use in learning Fiqh at MI Muhammadiyah Taraman. In terms of the effectiveness of using smar apps creator media on fiqh learning seen from the Pairet Sample Test, the 2 tailed sig value is 0.00, so there is an effect of giving the media, namely learning using smart apps creator in fiqh subjects is effective, Keywords: Learning Media, Smart Apps Creator, Learning Effectiveness